Adaptation of the geopolymer composite formulation binder to the shaping process. (December 2020) - Archez, J.; Texier-Mandoki, N.; Bourbon, X.; Caron, J.F.; Rossignol, S.
Graphical abstract: Highlights: Metakaolin-based geopolymer composites were synthetized with wollastonite and glass fibers. Feasbility of shaping was determined according to the formulation. Geopolymer composites were shaped with casting and robocasting process. Viscosity and mechanical properties of the formulations were mapped according to the shaping process. A castable and extrudable formulation presented compressive and bending strengths of 89 MPa and 15 MPa respectively. Abstract: This work aims to adapt a formulation of a geopolymer composite to elaborate complex shapes. Here a hollow cylinder is chosen to investigate different possible solutions: building process according to the formulation. To this end, different content of metakaolin, wollastonite, and glass fibers was used to identify the feasibility of shaping of the geopolymer composites. Hollow cylinder shape was elaborated from different formulations by casting and additive manufacturing (robocasting or Direct Ink Writing) regarding their feasibility. The mechanical properties of the formulations were then analyzed with thermal analysis, compressive and flexural tests, and compared with their way of shaping. The results showed that the viscosity can be mainly controlled by the wollastonite content. The formulations adapted to the robocasting present an optimal mechanical resistance due to a higher amount of reinforcement elements. A formulation that can be cast and robocast has been obtained and presents a compressive strength of 89 MPa and bending strength of 15 MPa. Thus, here some keys are given to design a formulation of geopolymer composite adapted to a shaping process by modifying the metakaolin, wollastonite, and glass fiber content.